Optimizing Formula of Fast Disintegrating Tablet of Belimbing Wuluh Leaf Extract with Crospovidone and Croscarmellose Sodium as Superdisintegrant - Citra Ariani Edityaningrum; Tantri Sofia Fauziah; Zainab Zainab; Hardi Astuti Witasari (Faculty of Pharmacy, Universitas Gadjah Mada, 2018)
Averrhoa bilimbi L. leaves can be used as an antidiabetic in the presence of flavonoid. Antidiabetic drugs were widely consumed by elderly patients who often had difficulty in consuming conventional tablets. Research in developing formulations of an antidiabetic drug that is capable of rapid disintegration and quickly dissolves when placed on the tounge is necessary, therefore it is formulated in fast disintegrating tablet dosage forms. The research aimed to formulate FDT of ethanol extract of Averrhoa bilimbi L. leaves with variation of superdisintegrant crospovidone and croscarmellose sodium. Fast disintegrating tablet of Averrhoa bilimbi L. leaves extract was manufactured by direct compression. Furthermore, the tablet was evaluated with physical properties and the results were analyzed using Design expert 10.1.3 program to bring in simplex lattice design (SLD) equation to get the optimum formula. Data which had been obtained was then analyzed byone sample test with confidence interval 95%. Based on the research results, the combinations of crospovidone and croscarmellose sodium was able to reduce the response of physical properties such as weight variation, hardness, friability, disintegration time, and wetting time. The optimum formula consist of 6.8 mg crospovidone and 12.2 mg croscarmellose sodium which resulted in 4.41 kg of hardness response, 0.59% of friability, 11.21 seconds of wetting time, and 3,85 seconds of disintegration time. Analysis of one sample t-test showed that there was no significant difference between the parameter values predicted results with the results of the research, so it can be concluded that SLD equation can be used to develop a formula that gives optimum parameters of FDT.